12‐4: 1000PPI LTPS OLED Display for VR Application. Issue 1 (25th September 2020) - Yu, Ziyang; Hu, Ming; Wang, Zhu; Liu, Guo; Wang, Bin; Jang, Peter; Wang, Dawei; Qiu, Haijun
Abstract : We developed 1000PPI OLED display based on LTPS to improve the RT and MPRT and solve the screen door effect. Different OLED pixel circuits including basic 3T1C and driving schemes consist of incessant and intermittent emission were compared and applied to achieve the key spec for VR applications. We studied the optical correction for Mura improvement and the driving TFT stabilization treatment for luminance depression optimization.